Replacement name for the genus Maublancia Bellamy, 1998 (Coleoptera, Buprestidae, Agrilinae), junior homonym of Maublancia Lepesme & Breuning, 1956 - Ponting, John (Zootaxa, 2018)
In 1947, Théry described a genus of buprestid beetle from Angola, naming it Maublancia Théry, 1947. He included two species in this genus; M. auberti Théry, 1947 and M. testui Théry, 1947. He did not, however, nominate a type species. Under Article 13.3 of the International Code of Zoological Nomenclature (1999) this name is not available.